161k views
5 votes
A classmate simplified a rational expression below

a) explain the error in this simplification
b) show your work as you correct the error

A classmate simplified a rational expression below a) explain the error in this simplification-example-1
User Henry Ruhs
by
4.6k points

1 Answer

1 vote

Part a)

Explain the error in this simplification.

Given the simplified expression


1-(2)/(x-2)=(x+1)/(x+2)


1-2\left(x+2\right)=\left(x+1\right)\left(x-2\right)


\:1-2x-4=x^2-x-2


-2x-3=x^2-x-2\:\:


0=x^2-2x-2\:\:


0=\left(x-1\right)\left(x-1\right)


x=1

Identifying the Main Error


1-(2)/(x-2)=(x+1)/(x+2)


1-2\left(x+2\right)=\left(x+1\right)\left(x-2\right) ← ERROR Starts here

Here is the Explanation of the Error


\mathrm{The\:equation\:should\:have\:been\:Multiplied\:by\:LCM=}\left(x-2\right)\left(x+2\right). In your case you wrongly multiply the equation.

CORRECTION

HERE IS HOW YOU SHOULD HAVE MULTIPLIED BY LCM = (x-2)(x+2):


1-(2)/(x-2)=(x+1)/(x+2)


1\cdot \left(x-2\right)\left(x+2\right)-(2)/(x-2)\left(x-2\right)\left(x+2\right)=(x+1)/(x+2)\left(x-2\right)\left(x+2\right)


\left(x-2\right)\left(x+2\right)-2\left(x+2\right)=\left(x+1\right)\left(x-2\right)

Part b)

Show your work as you correct the error

Here is the complete correction of the error.

Considering the expression


1-(2)/(x-2)=(x+1)/(x+2)


\mathrm{Find\:Least\:Common\:Multiplier\:of\:}x-2,\:x+2:\quad \left(x-2\right)\left(x+2\right)


1\cdot \left(x-2\right)\left(x+2\right)-(2)/(x-2)\left(x-2\right)\left(x+2\right)=(x+1)/(x+2)\left(x-2\right)\left(x+2\right)


\left(x-2\right)\left(x+2\right)-2\left(x+2\right)=\left(x+1\right)\left(x-2\right)


x^2-2x-8=x^2-x-2


x^2-2x-8+8=x^2-x-2+8


x^2-2x=x^2-x+6


-x=6


(-x)/(-1)=(6)/(-1)


x=-6

User AareP
by
4.4k points